2020
DOI: 10.1101/2020.04.19.20062174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher mortality in men from COVID19 infection-understanding the factors that drive the differences between the biological sexes

Abstract: The emergent global pandemic caused by the rapid spread of Severe Acute Respiratory syndrome-Coronavirus-2 (SARS-CoV-2) has led to increased mortality and negatively impacted day to day activities of humankind within a short period of time. As the data is rapidly emerging from earlier outbreak locations around the world, there are efforts to assimilate this with the knowledge from prior epidemics and find rapid solutions for this. One of the observations and a recurring theme is the disproportionate difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…13,20,21 Moreover, the random effects model yields an aggregate odds ratio (OR) of 1.84 for comparing the odds of death for males to females, maybe for possible sex differences in the immune response. 22 The reasons for the observed differences related to COVID-19 deaths are multifactorial. Another important factor is to consider is the stage of the epidemic in which the country finds itself.…”
Section: Discussionmentioning
confidence: 99%
“…13,20,21 Moreover, the random effects model yields an aggregate odds ratio (OR) of 1.84 for comparing the odds of death for males to females, maybe for possible sex differences in the immune response. 22 The reasons for the observed differences related to COVID-19 deaths are multifactorial. Another important factor is to consider is the stage of the epidemic in which the country finds itself.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Channappanavar et al (2017) found that the removal of the testes did not affect disease outcomes in male mice, whereas ovariectomy or treating female mice with the oestrogen receptor antagonists ICI-182 and ICI-780 resulted increased mortality to SARS-CoV infection, signifying that oestrogen signalling protects female mice from lethal SARS-CoV infection. In light of the recent pandemic situation, the same research team has stated that this could also be the reason for the male susceptibility to COVID-19 (Iyer et al 2020).…”
Section: Hypothetical Role Of 17b-oestradiol In Curbing Covid-19 Infementioning
confidence: 99%